"In Lui, Per Mezzo Di Lui, In Vista Di Lui" (Col 1,16): Un tentativo di sintesi della teologia della creazione contemporanea. - Rimoli, Emanuele (Miscellanea francescana, 2025)
The eighth centenary of the Canticle of the Creatures (1225-2025) offers the opportunity for a comprehensive synthesis between the systematic foundations of creation theology and contemporary magisterial developments. This study analyses the Christo-centric perspective of creation through the exegesis of the New Testament prepositions of Colossians 1:16 (in him, through him, to him), highlighting how Christ is simultaneously the ontological principle, the Trinitarian mediator, and the eschatological purpose of creation. The study shows how Pope Francis' teaching has brought about a theological-pastoral development of this cosmic Christology through the amplification of integral ecology as a soteriological category. An analysis of papal documents (Laudato si', Querida Amazonia, Laudate Deum) reveal the overcoming of modern dichotomies through a "situated anthropocentrism" that integrates personal salvation and cosmic redemption within the unity of the Trinitarian economy of salvation. The study also examines contemporary ecumenical convergences, particularly with the Orthodox theology of creation as a sacrament and Protestant eco-theologies, highlighting the guiding model of "life" proposed by Löning and Zenger as an alternative to the paradigm of progress. The Franciscan tradition, reinterpreted through authors such as Ilia Delio, emerges as a privileged bridge between medieval mysticism and contemporary scientific cosmology, confirming the central intuition of universal interconnectedness as a creaturely expression of the Trinitarian perichoresis.